Unravelling interactions between salt marsh evolution and sedimentary processes in the Wadden Sea (southeastern North Sea). (December 2014) - Schuerch, Mark; Dolch, Tobias; Reise, Karsten; Vafeidis, Athanasios T.
Salt marshes in the Wadden Sea constitute about 20% of all salt marshes along European coasts. They are of immense importance for coastal protection reasons and as habitat for coastal plant, bird, and invertebrate species. The Wadden Sea is a coastal sedimentary ecosystem in the southeastern North Sea. Besides salt marshes, it is composed of tidal flats, high sands, and sandy shoals, dissected by (sub)tidal channels and located behind barrier islands. Accelerated global sea-level rise (SLR) and changes in storm climate have been identified as possible threats for the persistence of the Wadden Sea ecosystem including its salt marshes. Moreover, it is known that the amount and composition of the sediment available for salt marshes are the most important parameters influencing their ability to adapt to current and future SLR. Assessing these parameters requires a thorough understanding of the sedimentary system of the salt marshes and the adjacent tidal basins. In the present review, we investigate and unravel the interactions of sedimentary processes in the Wadden Sea with the processes taking place on the salt marshes. We identify the most crucial processes and interactions influencing the morphological development of salt marshes in the Wadden Sea. A conceptual model is proposed, intended as a framework for improved understanding of salt marsh development and for incorporation into new salt marsh models. The proposed model may also be applicable to regions other than the Wadden Sea.